Sistem Retur Barang Pada Program Garansi Bebas Pengembalian di E-Commerce Shopee Perspektif Khiyar Syarat - Rohayati, Eti; Ja’far, A Kumedi; Faizal, Liky (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2025)
The development of digital technology has driven the rapid growth of the e-commerce sector, one of which is through the Shopee platform which provides a Free Return Guarantee program. This program aims to increase consumer confidence by giving the right to return goods if they do not match the description, are damaged, or for reasons of "changing your mind." However, in practice, this return mechanism raises problems, especially for sellers, such as the return of goods that do not meet the requirements, for example in damaged or used conditions. This problem creates an imbalance between the rights of buyers and sellers, making it interesting to study further. This study aims to analyse the mechanism for returning goods in the program using the perspective of khiyar kondisi in muamalah fiqh, which emphasizes fairness in transactions through mutual agreement terms, condition of goods, and clear duration. The research method used is a descriptive qualitative approach, with data obtained through documentation and interviews. Documentation includes a literature review related to the theory of khiyar kondisi and Shopee's return policy, while interviews were conducted with sellers and buyers to understand direct experiences related to this program. The results of the study show that the Shopee return mechanism meets several principles of khiyar kondisi, such as a clear return duration and agreement through platform terms. However, the main weaknesses lie in excessive flexibility, lack of strict verification of returned goods, and limited seller rights to reject returns of goods that do not meet the requirements. In conclusion, this program requires improvements in the return mechanism to create more balanced justice for buyers and sellers and to align the policy with the values of muamalah fiqh